Suitability of Tidal Swamp for Rubber Plantation in Three Villages of Ex Rice Mega Project, Pulang Pisau Regency, Central Kalimantan Province - M. A. Firmansyah; N. Yuliani; W.A. Nugroho; A. Bhermana (Jurnal Lahan Suboptimal : Journal of Suboptimal Lands, 2012)
Firmansyah et al. 2012. Suitability of Tidal Swamp for Rubber Plantation in Three Villages of Ex Rice Mega Project, Pulang Pisau Regency, Central Kalimantan Province. JLSO 1(2):149-157. Since 1920, tidal swamp has been widely developed for rubber plantation. Land rehabilitation of ex Mega Rice Project has attracted local community to cultivate the land for rubber plantation. The purpose of this research was to determine land suitability classification for rubber in tidal lowland areas located in three villages (Anjir Pulpis, Jabiren, and Sigi) in Pulang Pisau Regency wherein several types of soil were found, namely Sulfaquept, Endoaquepts, Dystrudept, and Haplohemist. The results indicated that there were several limiting factors to rubber plantation in tidal lowland, i.e. rooting condition, toxicity, nutrient retention, and peat land fire hazard. Actual land suitability classification felt into not suitable (N1) except Dystrudept of Jabiren which was classified as marginally suitable (S3). Improvements to overcome these limiting factors were required up to medium-high level. Low improvement level might not enhance land suitability class. Medium improvement level enhanced marginally suitable (S3) to moderately suitable (S2). Whilst, for high management level, it could enhance moderately suitable (S2) to highly suitable (S1). However, the development of tidal lowland for rubber plantation needed support from the government, especially the costly improvement of poor drainage system.